Cockroaches and Their Management - P.G. Koehler; B.E. Bayer; D. Branscome (EDIS)
This document provides a comprehensive guide on managing cockroaches in and around homes in Florida. It covers the identification of common species, their life cycles, and habitats. The document emphasizes integrated pest management (IPM) strategies, including prevention, sanitation, exclusion, and chemical control. It highlights the importance of eliminating water and food sources, sealing entry points, and using baits, sprays, and dusts effectively. The guide also stresses the need for proper pesticide use and safety precautions to ensure effective and sustainable cockroach control. Publication Date: January 1994.